Bad news about an old poison. A case of nicotine poisoning due to both ingestion and injection of the content of an electronic cigarette refill - Gianfranco Cervellin; Michele Luci; Carlotta Bellini; Giuseppe Lippi (Emergency Care Journal, 2013)
There are increasing concerns about the escalating use of electronic cigarettes (e-cigarettes). In particular, smokers have been advised by important agencies such as the US Food and Drug Administration about the potential harm to the health of these products, being now considered as drug delivery devices. The leading issues supporting this statement include the repeated inhalation of propylene glycol that is used as a diluent in refills, accidental poisoning, as well as evidence that ecigarettes may promote continued smoking since their use may compromise quitting motivations. Some authors have minimized these risks, considering the potential advantages of these devices for public health. Here we describe the first case of nicotine poisoning due to both ingestion and intravenous injection of the content of an e-cigarette refill, incorrectly mixed with methadone, bottled in a generic vial.